2019
DOI: 10.21475/ajcs.19.13.04.p1276
|View full text |Cite
|
Sign up to set email alerts
|

Screening of oil palm (Elaeis guineensis Jacq.) varieties for resistance to Curvularia leaf spot disease

Abstract: Leaf spot disease, particularly Curvularia leaf spot (CLS), can devastatingly damage both quality and quantity of oil palm seedlings in Thailand. Chemical fungicides have been intensively applied to control transmission of this disease. However, this has relatively low efficiency as the causative pathogen gains resistance to fungicides with selection pressure. An alternative or complementary cost-effective and environmentally friendly approach is necessary to find the resistant varieties for disease management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In contrast, lines 117, 129 and 155 presented low activities of both enzymes and were not significantly different (P ≤ 0.05) from the uninoculated controls in β-1,3glucanase activity (Table 1). Not only for enzyme activities results, but Kittimorakul et al (2019) also reported that lines 117, 129 and 155 were susceptible lines because of rapid manifestation of disease symptom (three days after inoculation), high disease score (3.10, 4.55 and 3.70) and high percentage of disease incidence (62%, 91% and 74%). Based on the enzyme activity results, two candidate lines were selected from the 10 lines tested.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, lines 117, 129 and 155 presented low activities of both enzymes and were not significantly different (P ≤ 0.05) from the uninoculated controls in β-1,3glucanase activity (Table 1). Not only for enzyme activities results, but Kittimorakul et al (2019) also reported that lines 117, 129 and 155 were susceptible lines because of rapid manifestation of disease symptom (three days after inoculation), high disease score (3.10, 4.55 and 3.70) and high percentage of disease incidence (62%, 91% and 74%). Based on the enzyme activity results, two candidate lines were selected from the 10 lines tested.…”
Section: Resultsmentioning
confidence: 93%
“…Ten different genotypes of oil palm tenera hybrid (Dura x Pisifera), lines 117, 129, 138, 155, 177, 187, 188, 202/6, 203 and 207, were initially selected from 124 lines by detached leaf method. Then, seedlings of these 10 genotypes were subjected to pathogenicity test to study their resistance against C. oryzae at the Oil Palm Agronomical Research Centre: Phase 2, Department of Plant Science, Faculty of Natural Resources, Prince of Songkla University, Thailand (Kittimorakul et al, 2019) to separate resistance and susceptible lines before further testing for enzyme activities. The seedlings chosen for this study were 3-4 months old, raised in the greenhouse conditions with temperature varying between of 25°C-30°C, 60% ± 5% relative humidity (RH), and 12 hr photoperiod.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Recently, the Sub-PSU1, the new variety of oil palm, has been released through a breeding programme, based on selecting the local parental hybrids from the genetic base in Southern Thailand. The Sub-PSU1 oil palm is a high-yielding tenera variety, well adapted to poor environmental conditions (Junsawang et al, 2020), i.e., drought stress (Duangpan et al, 2018), salt stress (Sukdee et al, 2022), and some progeny hybrids resistance to Curvularia leaf spot disease (Kittimorakul et al, 2019;. Thus, the seedling of Sub-PSU1 oil palm is increasingly required for new planting and replanting, and is encouraged to grow in Southern Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common diseases found in oil palm nurseries is leaf spot disease caused by phytopathogenic fungi. There are numerous phytopathogenic fungi that can cause leaf spot disease, most notably from the genus Curvularia (Kittimorakul et al, 2013, 2019; Sunpapao et al, 2014, 2018). The fungal spores of this pathogen are dispersed by water, wind, animals, insects and humans.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few studies have been conducted on generating oil palm varieties for leaf spot disease resistance (Kittimorakul et al, 2019); however, none are based on marker-assisted selection. Here we describe a GWAS for leaf spot disease resistance in oil palm, providing important resources, including potential candidate markers for the development of leaf spot disease-resistant oil palm varieties.…”
mentioning
confidence: 99%